Characterization of nutritional and health claims on the packaging of prepackaged sweetened beverages with the largest market share in Costa Rica - Miranda-Paguaga, Fabiola (2026)
Introduction: The increased consumption of sweetened beverages and its association with non-communicable diseases represents a major public health concern. Nutrition and health claims on product packaging may influence consumer perceptions and purchasing decisions. This study characterizes the claims present on the packaging of sweetened beverages available in the Costa Rican market and proposes recommendations for their improvement, considering the gaps identified in current regulations. Methods: A photographic record was made of the packaging of beverages offered by the three leading companies in the Costa Rican market (n=303), covering the following product categories: carbonated drinks (29.0%), iced teas (22.4%), drinkable yogurts (13.5%), soft drinks (9.2%), sweetened juices and nectars (7.9%), sports drinks (6.3%), energy drinks (5.9%), and flavored milks (5.6%). The presence of different types of claims (nutritional, health-related, and others) was coded according to definitions from international literature, as well as those established in the current national regulation (RTCA 67.01.60:10). Results: The most frequent claims were nutritional (95.7%). Product categories with the highest number of claims regulated under RTCA 67.01.60:10 were flavored milks, iced teas, sweetened nectars and juices, and drinkable yogurts. The number of claims identified according to national regulation was significantly lower than those identified using international definitions (p<0.005). Conclusion: A high proportion of claims was identified in the sample of beverages studied, many of which are not included in national regulations. It is essential to restrict the use of claims so that they serve an informative rather than promotional purpose, and to strengthen the capacity of regulatory authorities to assess claims not specified by current regulations.